Die Konvergenz Gegen Logarihmisch-Normale Verteilung - Bakštys, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Бакштис. Сходимость к логарифмически нормальному законуA. Bakštys. Konvergavimas prie logaritmiškai normalinio dėsnio